Działalność Dyrekcji Kolei Rzeszy w Opolu w świetle materiałów zachowanych w Archiwum Państwowym w Opolu. Przyczynek do historii Górnego Śląska po podziale regionu między Polskę i Niemcy w 1922 r. - Bereszyński, Zbigniew (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
One of the consequences of the division of Upper Silesia made in 1922 was the creation of two separate railway directorates: Directorate of German National Railway in Opole and the Directorate of Polish State Railways in Katowice. Both directorates cooperated in matters regarding the maintenance of local railroad routes and cross-border exchange and transit rail traffic. As a general rule, both sides strived to amicably settle possible problematic issues. It was easy to find common language, free of political prejudice, when discussing professional matters.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne